2019
DOI: 10.1002/pro.3662
|View full text |Cite
|
Sign up to set email alerts
|

NMR experiments redefine the hemoglobin binding properties of bacterial NEAr‐iron Transporter domains

Abstract: Iron is a versatile metal cofactor that is used in a wide range of essential cellular processes. During infections, many bacterial pathogens acquire iron from human hemoglobin (Hb), which contains the majority of the body's total iron content in the form of heme (iron protoporphyrin IX). Clinically important Gram-positive bacterial pathogens scavenge heme using an array of secreted and cell-wall-associated receptors that contain NEAr-iron Transporter (NEAT) domains. Experimentally defining the Hb binding prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Adding unlabeled tetrameric Hb that is saturated with heme (holo-Hb) to [U- 15 N] Shr H2 causes significant line broadening of its 1 H- 15 N heteronuclear single-quantum coherence (HSQC) spectrum, consistent with Shr H2 forming a high molecular weight complex with Hb (compare Fig. 2 A and B ) ( 19 , 29 ). Interestingly, the heme-capping interactions observed in the crystal structure are essential for receptor binding, as only minimal spectral changes are observed when Hb lacking heme (apo-Hb) is added to [U- 15 N] Shr H2 (compare Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Adding unlabeled tetrameric Hb that is saturated with heme (holo-Hb) to [U- 15 N] Shr H2 causes significant line broadening of its 1 H- 15 N heteronuclear single-quantum coherence (HSQC) spectrum, consistent with Shr H2 forming a high molecular weight complex with Hb (compare Fig. 2 A and B ) ( 19 , 29 ). Interestingly, the heme-capping interactions observed in the crystal structure are essential for receptor binding, as only minimal spectral changes are observed when Hb lacking heme (apo-Hb) is added to [U- 15 N] Shr H2 (compare Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Hb contains α- and β-globin chains that each bind to heme. Structures of isolated IsdB and IsdH NEAT domains free and bound to tetrameric Hb have revealed that residues within their aromatic motifs undergo a disordered-to-ordered transition upon binding, forming a 3 10 helix that interacts with the A- and E-helices in the globin ( Pilpa et al, 2006 ; Krishna Kumar et al, 2011 ; Kumar et al, 2014 ; Macdonald et al, 2019 ). Heme-binding NEAT domains feature a similarly located binding surface to engage heme.…”
Section: Hb Receptors: Neat Domains Can Work Together To Bind Hb and mentioning
confidence: 99%
“…The results of in vitro binding experiments have led to the conclusion that some NEAT domains from B. anthracis (IsdX1N and IsdX2N5) and L. monocytogenes (Hbp1N) bind to Hb, even though they lack a (F/Y)YH(Y/F) motif ( Ekworomadu et al, 2012 ; Honsa et al, 2013 ; Malmirchegini et al, 2014 ). However, recent NMR studies have raised doubts about these findings, because the Hb used in these prior studies was obtained from commercial sources that are now known to contain breakdown products that can lead to erroneous conclusions about Hb binding and Hb-dependent microbial growth ( Pishchany et al, 2013 ; Macdonald et al, 2019 ). Thus, at present, it appears that only NEAT domains containing a (F/Y)YH(Y/F) motif function as Hb receptors.…”
Section: Neat Domains In Other Species Of Gram-positive Bacteriamentioning
confidence: 99%
“…For Hb binding, ELISA experiments have been the main demonstrative tool. C. diphtheriae proteins HtaA and ChtB [34] [36], B. anthracis proteins IsdX1/X2 [57] and L. monocytogenes protein Hbp2 [63] are examples ELISA demonstrated Hb binding but follow up NMR experiments aimed at detecting haem binding directly failed to detect an Hb interaction for B. anthracis IsdX1/X2 [123]. One plausible explanation for this discrepancy is that in most ELISA experiments, the Hb used, usually commercially bought, contains a variety of breakdown products including multiple oligomeric and oxidation states and that immobilisation of In addition to this, there must be clarity when describing the ability of aforementioned Hb binding proteins to actually engage in the actively stripping of haem from Hb.…”
Section: Intimacy Of Interactions With Hbmentioning
confidence: 99%